Diabetes and increased lipid peroxidation are associated with systemic inflammation even in well-controlled patients - de Souza Bastos, Alliny [UNESP]; Graves, Dana T.; de Melo Loureiro, Ana Paula; Júnior, Carlos Rossa [UNESP]; Corbi, Sâmia Cruz Tfaile [UNESP]; Frizzera, Fausto; Scarel-Caminaga, Raquel Mantuaneli [UNESP]; Câmara, Niels Olsen; Andriankaja, Oelisoa M.; Hiyane, Meire I.; Orrico, Silvana Regina Perez [UNESP] (Elsevier, 2016)
Background The effect of the interaction between type 2 diabetes and dyslipidemia on inflammation and lipid peroxidation (LPO) has not been assessed. Aim To investigate whether diabetes coupled with dyslipidemia alters oxidative metabolism leading to increased LPO products and inflammatory status. Methods 100 patients were divided into four groups based upon diabetic and dyslipidemic status: poorly controlled diabetes with dyslipidemia (DM-PC/D), well-controlled diabetes with dyslipidemia (DM-WC/D), normoglycemic individuals with dyslipidemia (NG/D), and normoglycemic individuals without dyslipidemia (NG/ND). Plasma was evaluated for an LPO product (MDA), antioxidant levels and inflammatory cytokines. Results Diabetics presented significantly higher levels of LPO (p < 0.05) and the DM-PC/D had higher levels of proinflammatory cytokines and MDA in the plasma in comparison with normoglycemics (p < 0.05). Interestingly IL1-β, IL-6, and TNF-α in DM-WC/D were not statistically different from those in DM-PC/D. Normoglycemic individuals with dyslipidemia presented significantly increased levels of IL-6 and TNF-α when compared to normoglycemic without dyslipidemia (p < 0.05). MDA levels were also positively correlated with the presence of DM complications (r = 0.42, p < 0.01). Conclusions These findings show that dyslipidemia is associated with an increased inflammatory status, even in well-controlled diabetics and in normoglycemics. Our results suggest that lipid metabolism and peroxidation are important for the development of inflammation, which is elevated in several complications associated with diabetes.
Keywords: Cytokines; Diabetes mellitus type 2; Dyslipidemia; Inflammation; Lipid peroxidation